Maggot extracts chemo-prevent inflammation and tumorigenesis accompanied by changes in the intestinal microbiome and metabolome in AOM/DSS-induced mice - Tang, Xun; Wang, Lei; Wang, Daojuan; Zhang, Yi; Wang, Tingyu; Zhu, Zhengquan; Weng, Yajing; Tao, Gaojian; Wang, Qin; Tang, Li; Yan, Feng; Wang, Yong (Frontiers in Microbiology, 2023)
Inflammatory responses and intestinal microbiome play a crucial role in the progression of colitis-associated carcinoma (CAC). The traditional Chinese medicine maggot has been widely known owing to its clinical application and anti-inflammatory function. In this study, we investigated the preventive effects of maggot extract (ME) by intragastric administration prior to azoxymethane (AOM) and dextran sulfate sodium (DSS) induced CAC in mice. Results showed that ME had superior positions in ameliorating body weight lost, disease activity index score, splenomegaly, colon length reduction, intestinal barrier damage and colonic inflammation, in comparison with the AOM/DSS group. The number and size of polypoid colonic tumors were decreased after pre-administration of ME. In addition, ME was found to reverse the downregulation of tight junction proteins (zonula occluden-1 and occluding) while suppress the levels of inflammatory factors (IL-1 and IL-6) in models. Moreover, Toll-like receptor 4 (TLR4) mediated intracellular nuclear factor-B (NF-B)-containing signaling cascades, including inducible nitric oxide synthase and cyclooxygenase-2, exhibited decreasing expression in model mice after ME pre-administration. 16s rRNA analysis and untargeted-metabolomics profiling of fecal samples inferred that ME revealed an ideal prevention of intestinal dysbiosis in CAC mice, accompanied by and correlated with alterations in the composition of metabolites. Overall, ME pre-administration might be a chemo-preventive candidate in the initiation and development of CAC.